1990
DOI: 10.1521/jscp.1990.9.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Images: Effects of the Standard of Beauty on the Self- and Body-Esteem of Women Exhibiting Varying Levels of Bulimic Symptoms

Abstract: Authors in the field of eating disorders suggest that increasing preferences for thin body shapes in women may be related to recent increases in the prevalence of eating-related problems. Using a social comparison theory paradigm, this study looked at the impact of exposure to slides of thin, average, and oversize models on the self-evaluations of 162 women exhibiting varying levels of self-reported bulimic symptoms. Contrary to the author's expectations, exposure to thin models was related to lower self-evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
208
4
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(230 citation statements)
references
References 18 publications
13
208
4
4
Order By: Relevance
“…For example, it would be interesting to investigate the effects of in vivo social comparison processes with peers. To achieve this, one might manipulate the appearance of the confederate but hold the verbal interchange constant to determine whether exposure to attractive peers produces the increases in body dissatisfaction and negative affect observed in studies that expose women to media-portrayed thin-ideal images (e.g., Irving, 1990). Future research should also investigate in greater detail the factors that may amplify or mitigate the effects of social pressure to be thin or social comparison processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it would be interesting to investigate the effects of in vivo social comparison processes with peers. To achieve this, one might manipulate the appearance of the confederate but hold the verbal interchange constant to determine whether exposure to attractive peers produces the increases in body dissatisfaction and negative affect observed in studies that expose women to media-portrayed thin-ideal images (e.g., Irving, 1990). Future research should also investigate in greater detail the factors that may amplify or mitigate the effects of social pressure to be thin or social comparison processes.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized experiments more effectively rule out this possibility, although they can have limited external validity. Experiments have found that exposure to ultra-slender media images results in acute increases in body dissatisfaction and negative affect among young adult females (Cash, Cash, & Butters, 1983;Irving, 1990;Pinhas, Toner, Ali, Garfinkel, & Stuckless, 1999;Posavac, Posavac, & Weigel, 2001;Richins, 1991;Stice & Shaw, 1994). For example, one study found that a 3-minute exposure to thin-ideal images from a fashion magazine, compared with control images, resulted in increased depression, shame, guilt, stress, insecurity, and body dissatisfaction (Stice & Shaw, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The pursuit and internalization of unrealistic ideals of thinness (the "thin ideal") may be attributable in part to repeated exposure to and internalization of message that glamorize and glorify excessive thinness (Irving, 1990;Stice, Schupak-Neuberg, Shaw, & Stein, 1994). Increased acceptance of these sociocultural messages that advertise the "superwoman ideal," a female who overachieves in beauty, relationships, and career, may lead to confusion regarding role expectations (Steiner-Adair, 1994).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Specifically, portrayals of feminine beauty and success in the media are believed to have an important influential role in the process of females internalizing the thin-ideal . In one study, Irving (1990) showed slides of thin, average, and overweight models to different group of female undergraduates. Following these "slide shows," it was found that the group of females that viewed the thin models experienced significantly lower body satisfaction than the females who were exposed to the slides of average or overweight models.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation